A new method for ultra-high temperature degreasing of ceramics

Through the new ceramic ultra-high temperature degreasing method, the problems of high hardness and poor conductivity of silicon carbide ceramic composite materials during processing are solved, uniform distribution of materials and efficient degreasing are achieved, and the comprehensive performance of new ceramics is improved.

CN119735441AInactive Publication Date: 2025-04-01穆智(上海)新能源科技有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411912484.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing silicon carbide ceramic composite materials have problems of high hardness and poor conductivity during processing, which makes it difficult to achieve rapid and precise processing, limiting their application in aviation, aerospace and other industries.

Method used

A new ceramic ultra-high temperature degreasing method is adopted to ball mill the silicon carbide, bentonite, sintering aid and sintering aid, and after mixing evenly, the ceramic blank is prepared by semi-dry press forming method, and degreasing and pre-sintering at high temperatures through ultrasonic vibration, and finally high-temperature sintering is performed under vacuum or inert gas conditions.

Benefits of technology

The uniform distribution and efficient degreasing of silicon carbide ceramic composite materials have been achieved, and the toughness, bending resistance, hardness, wear resistance and oxidation resistance of new ceramics have been improved. The overall strength and impact toughness have been significantly improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of silicon carbide ceramics. The present invention discloses a novel ultra-high temperature degreasing method for ceramics, comprising the following steps: 1) material preparation, 2) mixing, 3) blanking, 4) degreasing and pre-sintering, and 5) sintering. The green blanks that have undergone the thermal degreasing and pre-sintering are placed in a sintering furnace, and are subjected to high temperature sintering according to a two-stage heating program under vacuum or inert gas conditions to obtain the novel ceramics. The silicon carbide of the present invention is evenly distributed in the ceramic system, and the voids are evenly distributed. The novel ceramics organically combine toughness and bending resistance with the high hardness, high wear resistance, corrosion resistance, and oxidation resistance of the ceramics, and the overall strength, impact toughness, and wear resistance are greatly improved, and the wear resistance consistency is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silicon carbide ceramics, and in particular to a novel ultra-high temperature degreasing method for ceramics. Background Art

[0002] Silicon carbide ceramics and their composite materials are widely used in various industries such as aviation, aerospace, and nuclear industry, such as heat exchangers, microchannel reactors, semiconductor hardware (suction cups / guide rails / platforms), high-power devices, optical application components, etc. Conventional silicon carbide ceramics and their composite materials have high hardness and need to be processed by diamond, which makes processing and molding difficult. At the same time, their poor electrical conductivity makes it difficult to meet the requirements of electric spark machining. The difficulty in achieving fast and precise processing of silicon carbide ceramic composite materials is one of the main bottlenecks restricting the application of silicon carbide ceramic composite materials.

[0003] The degreasing process is the most important stage in the preparation of ceramics, which determines the quality of the final product to a certain extent. This is because most of the defects in ceramic materials are formed in the degreasing stage, such as cracks, pores, deformation, bubbling, etc., and the defects generated in the degreasing process cannot be compensated by the later sintering stage.

[0004] Therefore, a new ultra-high temperature degreasing method for ceramics is needed to solve the above problems. Summary of the invention

[0005] The present invention provides a novel ultra-high temperature degreasing method for ceramics to solve the problems in the above-mentioned background technology. The solution of the present invention is:

[0006] A novel ultra-high temperature degreasing method for ceramics comprises the following steps:

[0007] 1) ball-milling silicon carbide, bentonite, sintering aid and sintering aid to a particle size of ≤20 μm to obtain a primary material; the mass ratio of silicon carbide, bentonite, sintering aid and sintering aid is 10:1:0.1-1:0.05-0.1;

[0008] 2) The primary material, adhesive, dispersant and solvent are mixed uniformly, and the material is trapped at room temperature for 12 to 24 hours to obtain a mold material; the solvent is ethanol, and the mass ratio of the primary material, adhesive, dispersant and solvent is 50 to 150:20 to 30:2 to 10:50 to 120;

[0009] 3) placing the mold material into a mold, pressing and molding it by a semi-dry pressing method, placing it in a drying furnace, and drying it at 100-120° C. to obtain a ceramic blank;

[0010] 4) Degreasing, immersing the ceramic blank in a soaking solution at 55-60°C, ultrasonically vibrating, with a vibration frequency of 20-30KHz, a vibration time of 10-20min, and a soaking time of 10-30min. After soaking, take it out, add steam and heat it to 300-360°C at a heating rate of 3°C / min, and keep it warm for 0.3-0.7 hours; after taking it out, place it in a room temperature environment without ventilation for more than 24 hours, and then move it into an oven for drying; the dried blank is placed in a muffle furnace, and thermal degreasing and pre-sintering are performed according to a one-stage temperature control program;

[0011] 5) Sintering, placing the green body after the thermal debinding and pre-sintering in a sintering furnace, and performing high-temperature sintering according to a two-stage temperature increase program under vacuum or inert gas conditions to obtain the novel ceramic.

[0012] As a preferred technical solution, the sintering aid is at least one of aluminum nitride, boron nitride, silicon oxide, aluminum oxide, yttrium oxide, zirconium oxide, strontium oxide, strontium carbonate, silicon dioxide, ferric oxide, cerium oxide, and lanthanum oxide.

[0013] As a preferred technical solution, the fixing agent is one of citric acid, p-toluenesulfonic acid, pentosine or oxalic acid.

[0014] As a preferred technical solution, the preparation method of the sintering auxiliary material is: graphene and asphalt-based carbon fiber are mixed in a mass ratio of 100:5-10, and stirred and heat-treated at 400-600°C to obtain graphene with asphalt carbon fiber attached to the surface; the particle size of the graphene is ≤20μm;

[0015] Graphene with asphalt carbon fiber attached to the surface is mixed with glass fiber in a mass ratio of 1 to 2:45, and heat treated at 1000 to 1200°C for 2 to 3 hours to obtain a sintering auxiliary material, wherein the particle size of the glass fiber is 4 to 10 μm, and the length of the glass fiber is 0.05 to 0.1 mm.

[0016] As a preferred technical solution, the adhesive is a plurality of polyvinyl alcohol, yellow dextrin, sodium silicate, sodium tripolyphosphate, carboxymethyl cellulose, silica sol and a resin with a residual carbon value greater than 35%.

[0017] As a preferred technical solution, the dispersant includes stearic acid, polyvinyl pyrrolidone, and sodium dodecylbenzene sulfonate.

[0018] As a preferred technical solution, the soaking solution includes deionized water, isoascorbic acid, ammonium dodecylbenzenesulfonate and sodium silicate, and the mass ratio thereof is 1000:10-20:0.1-0.5:1-3.

[0019] As a preferred technical solution, the one-stage temperature control program for thermal debinding and pre-sintering is to heat up to 500-550°C at a heating rate of 2°C / min and keep it warm for 0.5-1.5 hours; to heat up to 1000-1200°C at a heating rate of 5°C / min and keep it warm for 1-3 hours;

[0020] The two-stage heating program is to heat up to 1600-1700 degrees Celsius at a heating rate of 5°C / min and keep it warm for 5-15 minutes; to heat up to 1900-2100°C at a heating rate of 5°C / min and keep it warm for 1-3 hours; to cool down from 2000°C to 1000°C at a cooling rate of 5°C / min; and to cool naturally in the sintering furnace.

[0021] Due to the adoption of the above technical scheme, a novel ceramic ultra-high temperature degreasing method comprises the following steps: 1) material preparation, ball milling silicon carbide, bentonite, sintering aid and sintering aid, ball milling to a particle size of ≤20 μm, to obtain a primary material; the mass ratio of the silicon carbide, bentonite, sintering aid and sintering aid is 10:1:0.1-1:0.05-0.1; 2) mixing, uniformly mixing the primary material, adhesive, dispersant and solvent, trapping the material at room temperature, trapping the material for 12-24 hours, to obtain a mold material; the solvent is ethanol, and the mass ratio of the primary material, adhesive, dispersant and solvent is 50-150:20-30:2-10:50-120; 3) blanking, placing the mold material into a mold, pressing and molding by a semi-dry pressing method, placing it in a drying furnace, and drying it at 100-1 The ceramic blank is dried at 20°C to obtain a ceramic blank; 4) degreasing and pre-sintering, the ceramic blank is immersed in an immersion solution at 55-60°C, ultrasonically vibrated, the vibration frequency is 20-30KHz, the vibration time is 10-20min, and the immersion time is 10-30min. After the immersion is completed, it is taken out, steam is added to heat the temperature to 300-360°C at a heating rate of 3°C / min, and the temperature is kept for 0.3-0.7 hours; after taking out, it is placed in an airtight room temperature environment for drying for more than 24 hours, and then moved into an oven for drying; the dried blank is placed in a muffle furnace, and thermal degreasing and pre-sintering are performed according to a one-stage temperature control program; 5) sintering, the green blank that has undergone the thermal degreasing and pre-sintering is placed in a sintering furnace, and high-temperature sintering is performed under vacuum or inert gas conditions according to a two-stage heating program to obtain the novel ceramic.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] Silicon carbide is evenly distributed in the ceramic system, and the voids are evenly distributed. The new ceramic organically combines toughness and bending resistance with high hardness, high wear resistance, corrosion resistance and oxidation resistance of ceramics. The overall strength, impact toughness and wear resistance are greatly improved, and the wear resistance consistency is good.

[0024] The method of the invention has the advantages of fast degreasing speed, short time, low cost, simple operation, strong practicability and thorough degreasing in degreasing. DETAILED DESCRIPTION

[0025] The invention provides a novel ultra-high temperature degreasing method for ceramics.

[0026] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0027] Example 1

[0028] 1) ball-milling silicon carbide, bentonite, sintering aid and sintering aid to a particle size of ≤20 μm to obtain a primary material; the mass ratio of silicon carbide, bentonite, sintering aid and sintering aid is 10:1:0.1:0.05;

[0029] 2) The primary material, adhesive, dispersant and solvent are mixed uniformly, and the material is trapped at room temperature for 12 hours to obtain a mold material; the solvent is ethanol, and the mass ratio of the primary material, adhesive, dispersant and solvent is 50:20:2:52;

[0030] 3) placing the mold material into a mold, pressing and molding it by a semi-dry pressing method, placing it in a drying furnace, and drying it at 100-120° C. to obtain a ceramic blank;

[0031] 4) Degreasing, immersing the ceramic blank in a soaking solution at 55°C, ultrasonically vibrating at a frequency of 20KHz, for 10 minutes, and soaking for 10 minutes. After soaking, take it out, add steam and heat it to 300°C at a heating rate of 3°C / min, and keep it warm for 0.3 hours; after taking it out, place it in a room temperature environment without ventilation for more than 24 hours, and then move it into an oven for drying; the dried blank is placed in a muffle furnace, and hot degreasing and pre-sintering are performed according to a one-stage temperature control program;

[0032] 5) Sintering, placing the green body after the thermal debinding and pre-sintering in a sintering furnace, and performing high-temperature sintering according to a two-stage temperature increase program under vacuum or inert gas conditions to obtain the novel ceramic.

[0033] The sintering aid is aluminum nitride.

[0034] The fixing agent is citric acid.

[0035] The preparation method of the sintering auxiliary material is as follows: graphene and asphalt-based carbon fiber are mixed in a mass ratio of 100:5, and stirred and heat-treated at 400° C. to obtain graphene with asphalt-based carbon fiber attached to the surface; the particle size of the graphene is ≤20 μm;

[0036] Graphene with asphalt carbon fiber attached to the surface is mixed with glass fiber in a mass ratio of 1 to 2:45, and heat treated at 1000°C for 2 hours to obtain a sintering auxiliary material, wherein the particle size of the glass fiber is 4 to 10 μm, and the length of the glass fiber is 0.05 to 0.1 mm.

[0037] The adhesive is composed of polyvinyl alcohol, carboxymethyl cellulose, silica sol and resin with a residual carbon value greater than 35%, and the mass ratio is 5:2:4. The resin with a residual carbon value greater than 35% is prepared by mixing phenolic resin and ethanol in a mass ratio of 1:1.

[0038] The dispersant includes stearic acid, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate, and the mass ratio thereof is 0.8:1.1:1.1.

[0039] The soaking solution includes deionized water, isoascorbic acid, ammonium dodecylbenzenesulfonate and sodium silicate, and the mass ratio thereof is 1000:10:0.1:1.

[0040] The first-stage temperature control program for thermal debinding and pre-sintering is to increase the temperature to 500°C at a heating rate of 2°C / min and keep it at that temperature for 0.5 hours; increase the temperature to 1000°C at a heating rate of 5°C / min and keep it at that temperature for 1 hour;

[0041] The two-stage heating program is to heat up to 1600 degrees Celsius at a heating rate of 5°C / min and keep it warm for 5 minutes; heat up to 1900°C at a heating rate of 5°C / min and keep it warm for 1 hour; cool down to 1000°C at a cooling rate of 5°C / min; and cool naturally in the sintering furnace.

[0042] After the first stage of temperature control, a 9.5mm thick blank was sampled and cooled. After observation and testing, the appearance and internal structure were intact, and the degreasing rate reached 99.9%.

[0043] The new ceramic prepared in this embodiment was tested for performance, and the three-point bending strength was 470Mpa and the fracture toughness was 2.5Mpam. 1 / 2 .

[0044] Example 2

[0045] 1) ball-milling silicon carbide, bentonite, a sintering aid and a sintering aid to obtain a primary material; the mass ratio of silicon carbide, bentonite, a sintering aid and a sintering aid is 10:1:1:0.1;

[0046] 2) The primary material, adhesive, dispersant and solvent are mixed uniformly, and the material is trapped at room temperature for 24 hours to obtain a mold material; the solvent is ethanol, and the mass ratio of the primary material, adhesive, dispersant and solvent is 150:30:10:120;

[0047] 3) placing the mold material into the mold, pressing and molding by semi-dry pressing, placing it in a drying furnace, and drying it at 100° C. to obtain a ceramic blank;

[0048] 4) Degreasing, immersing the ceramic blank in a soaking solution at 55-60°C, ultrasonically vibrating, with a vibration frequency of 30KHz, a vibration time of 20min, and a soaking time of 30min. After soaking, take it out, add steam and heat it to 360°C at a heating rate of 3°C / min, and keep it warm for 0.7 hours; after taking it out, place it in a room temperature environment without ventilation for more than 24 hours, and then move it into an oven for drying; the dried blank is placed in a muffle furnace, and hot degreasing and pre-sintering are performed according to a one-stage temperature control program;

[0049] 5) Sintering, placing the green body after the thermal debinding and pre-sintering in a sintering furnace, and performing high-temperature sintering according to a two-stage temperature increase program under vacuum or inert gas conditions to obtain the novel ceramic.

[0050] The sintering aids are aluminum oxide and zirconium oxide.

[0051] The fixing agent is lodoxine.

[0052] The preparation method of the sintering auxiliary material is as follows: graphene and asphalt-based carbon fiber are mixed in a mass ratio of 100:10, and stirred and heat-treated at 600° C. to obtain graphene with asphalt-based carbon fiber attached to the surface; the particle size of the graphene is ≤20 μm;

[0053] Graphene with asphalt carbon fiber attached to the surface is mixed with glass fiber in a mass ratio of 2:45, and heat treated at 1200°C for 3 hours to obtain a sintering auxiliary material. The particle size of the glass fiber is 4 to 10 μm, and the length of the glass fiber is 0.05 to 0.1 mm.

[0054] The adhesive is polyvinyl alcohol, yellow dextrin and sodium silicate.

[0055] The dispersant includes stearic acid, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate, and the mass ratio thereof is 1.2:1.4:1.3.

[0056] The soaking solution includes deionized water, isoascorbic acid, ammonium dodecylbenzenesulfonate and sodium silicate, and the mass ratio thereof is 1000:20:0.5:3.

[0057] The first-stage temperature control program for thermal debinding and pre-sintering is to increase the temperature to 550°C at a heating rate of 2°C / min and keep it at that temperature for 1.5 hours; increase the temperature to 1200°C at a heating rate of 5°C / min and keep it at that temperature for 3 hours;

[0058] The two-stage heating program is to heat up to 1700 degrees Celsius at a heating rate of 5°C / min and keep it warm for 15 minutes; to heat up to 2100°C at a heating rate of 5°C / min and keep it warm for 3 hours; to cool from 2000°C to 1000°C at a cooling rate of 5°C / min; and to cool naturally in the sintering furnace.

[0059] After the first stage of temperature control, a 9.5mm thick blank was sampled and cooled. After observation and testing, the appearance and internal structure were intact, and the degreasing rate reached 99.9%.

[0060] The new ceramic prepared in this embodiment was tested for performance, and the three-point bending strength was 504Mpa and the fracture toughness was 2.4Mpam. 1 / 2 .

[0061] Example 3

[0062] 1) ball-milling silicon carbide, bentonite, sintering aid and sintering aid to a particle size of ≤20 μm to obtain a primary material; the mass ratio of silicon carbide, bentonite, sintering aid and sintering aid is 10:1:0.3:0.06;

[0063] 2) The primary material, adhesive, dispersant and solvent are mixed uniformly, and the material is trapped at room temperature for 10 hours to obtain a mold material; the solvent is ethanol, and the mass ratio of the primary material, adhesive, dispersant and solvent is 120:25:7:100;

[0064] 3) placing the mold material into a mold, pressing and molding it by a semi-dry pressing method, placing it in a drying furnace, and drying it at 110° C. to obtain a ceramic blank;

[0065] 4) Degreasing, immersing the ceramic blank in a soaking solution at 60°C, ultrasonically vibrating, with a vibration frequency of 30KHz, a vibration time of 15min, and a soaking time of 20min. After soaking, take it out, add steam and heat it to 350°C at a heating rate of 3°C / min, and keep it warm for 0.5 hours; after taking it out, place it in a room temperature environment without ventilation for more than 24 hours, and then move it into an oven for drying; the dried blank is placed in a muffle furnace, and hot degreasing and pre-sintering are performed according to a one-stage temperature control program;

[0066] 5) Sintering, placing the green body after the thermal debinding and pre-sintering in a sintering furnace, and performing high-temperature sintering according to a two-stage temperature increase program under vacuum or inert gas conditions to obtain the novel ceramic.

[0067] The sintering aids are aluminum nitride and cerium oxide.

[0068] The fixing agent is p-toluenesulfonic acid.

[0069] The preparation method of the sintering auxiliary material is as follows: graphene and asphalt-based carbon fiber are mixed in a mass ratio of 100:7, and stirred and heat-treated at 600° C. to obtain graphene with asphalt-based carbon fiber attached to the surface; the particle size of the graphene is ≤20 μm;

[0070] Graphene with asphalt carbon fiber attached to the surface is mixed with glass fiber in a mass ratio of 2:45, and heat treated at 1100°C for 2 hours to obtain a sintering auxiliary material, wherein the particle size of the glass fiber is 4 to 10 μm, and the length of the glass fiber is 0.05 to 0.1 mm.

[0071] The adhesive is polyvinyl alcohol, sodium silicate, carboxymethyl cellulose, silica sol and a resin with a residual carbon value greater than 35%, and the mass ratio thereof is 11:3:1:1.5:10; the resin with a residual carbon value greater than 35% is prepared by mixing phenolic resin and ethanol in a mass ratio of 1:1.

[0072] The dispersant includes stearic acid, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate in a mass ratio of 1:1.2:1.2.

[0073] The soaking solution includes deionized water, isoascorbic acid, ammonium dodecylbenzenesulfonate and sodium silicate, and the mass ratio thereof is 1000:15:0.3:2.

[0074] The first-stage temperature control program for thermal debinding and pre-sintering is to increase the temperature to 550°C at a heating rate of 2°C / min and keep it at that temperature for 0.5 to 1.5 hours; increase the temperature to 1200°C at a heating rate of 5°C / min and keep it at that temperature for 3 hours;

[0075] The two-stage heating program is to heat up to 1600 degrees Celsius at a heating rate of 5°C / min and keep it warm for 15 minutes; to heat up to 2000°C at a heating rate of 5°C / min and keep it warm for 3 hours; to cool from 2000°C to 1000°C at a cooling rate of 5°C / min; and to cool naturally in the sintering furnace.

[0076] After the first stage of temperature control, a 9.5mm thick blank was sampled and cooled. After observation and testing, the appearance and internal structure were intact, and the degreasing rate reached 99.9%.

[0077] The new ceramic prepared in this embodiment was tested for performance, and the three-point bending strength was 545Mpa and the fracture toughness was 2.5Mpam. 1 / 2 .

[0078] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A novel ultra-high temperature degreasing method for ceramics, characterized in that: The following steps are involved: 1) ball-milling silicon carbide, bentonite, sintering aid and sintering aid to a particle size of ≤20 μm to obtain a primary material; the mass ratio of silicon carbide, bentonite, sintering aid and sintering aid is 10:1:0.1-1:0.05-0.1; 2) The primary material, adhesive, dispersant and solvent are mixed uniformly, and the material is trapped at room temperature for 12 to 24 hours to obtain a mold material; the solvent is ethanol, and the mass ratio of the primary material, adhesive, dispersant and solvent is 50 to 150:20 to 30:2 to 10:50 to 120; 3) placing the mold material into a mold, pressing and molding it by a semi-dry pressing method, placing it in a drying furnace, and drying it at 100-120° C. to obtain a ceramic blank; 4) Degreasing, immersing the ceramic blank in a soaking solution at 55-60°C, ultrasonically vibrating, with a vibration frequency of 20-30KHz, a vibration time of 10-20min, and a soaking time of 10-30min. After soaking, take it out, add steam and heat it to 300-360°C at a heating rate of 3°C / min, and keep it warm for 0.3-0.7 hours; after taking it out, place it in a room temperature environment without ventilation for more than 24 hours, and then move it into an oven for drying; the dried blank is placed in a muffle furnace, and thermal degreasing and pre-sintering are performed according to a one-stage temperature control program; 5) Sintering, placing the green body after the thermal debinding and pre-sintering in a sintering furnace, and performing high-temperature sintering according to a two-stage temperature increase program under vacuum or inert gas conditions to obtain the novel ceramic.

2. A novel ultra-high temperature degreasing method for ceramics as claimed in claim 1, characterized in that: The sintering aid is at least one of aluminum nitride, boron nitride, silicon oxide, aluminum oxide, yttrium oxide, zirconium oxide, strontium oxide, strontium carbonate, silicon dioxide, ferric oxide, cerium oxide, and lanthanum oxide.

3. A novel ultra-high temperature degreasing method for ceramics as claimed in claim 1, characterized in that: The fixing agent is one of citric acid, p-toluenesulfonic acid, pentosan or oxalic acid.

4. A novel ultra-high temperature degreasing method for ceramics as claimed in claim 1, characterized in that: The preparation method of the sintering auxiliary material is as follows: graphene and asphalt-based carbon fiber are mixed in a mass ratio of 100:5-10, and stirred and heat-treated at 400-600° C. to obtain graphene with asphalt carbon fiber attached to the surface; the particle size of the graphene is ≤20 μm; Graphene with asphalt carbon fiber attached to the surface is mixed with glass fiber in a mass ratio of 1 to 2:45, and heat treated at 1000 to 1200°C for 2 to 3 hours to obtain a sintering auxiliary material, wherein the particle size of the glass fiber is 4 to 10 μm, and the length of the glass fiber is 0.05 to 0.1 mm.

5. A novel ultra-high temperature degreasing method for ceramics as claimed in claim 1, characterized in that: The adhesive is multiple types of polyvinyl alcohol, yellow dextrin, sodium silicate, sodium tripolyphosphate, carboxymethyl cellulose, silica sol and resin with a residual carbon value greater than 35%.

6. A novel ultra-high temperature degreasing method for ceramics as claimed in claim 1, characterized in that: The dispersant includes stearic acid, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate.

7. A novel ultra-high temperature degreasing method for ceramics as claimed in claim 1, characterized in that: The soaking solution comprises deionized water, isoascorbic acid, ammonium dodecylbenzenesulfonate and sodium silicate, and the mass ratio thereof is 1000:10-20:0.1-0.5:1-3.

8. A novel ultra-high temperature degreasing method for ceramics as claimed in claim 1, characterized in that: The first-stage temperature control program for thermal debinding and pre-sintering is to increase the temperature to 500-550°C at a heating rate of 2°C / min and keep it warm for 0.5-1.5 hours; increase the temperature to 1000-1200°C at a heating rate of 5°C / min and keep it warm for 1-3 hours; The two-stage heating program is to heat up to 1600-1700 degrees Celsius at a heating rate of 5°C / min and keep it warm for 5-15 minutes; to heat up to 1900-2100°C at a heating rate of 5°C / min and keep it warm for 1-3 hours; to cool down from 2000°C to 1000°C at a cooling rate of 5°C / min; and to cool naturally in the sintering furnace.

Citation Information

Cited By

  • Preparation method of high-strength ceramic

    CN121135449A

  • A method for preparing high-strength ceramics

    CN121135449B